1985
DOI: 10.1177/028418518502600621
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Media Osmolality and Plasma Volume Changes

Abstract: A theoretical and experimental study of the plasma volume expansion consequent on the hyperosmolality of contrast media is presented. In the case of the ratio 1.5 media theory and experiment coincide closely but in the case of the ratio 3 media the observed changes exceed the predicted. It is proposed that this is due partly to the slower diffusion of the ratio 3 media out of the intravascular space and partly due to the fact that the osmotic load presented by these media is greater than would be expected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The late tendency for increased cardiac output is in agreement with data from other trials [2,34,38], and is also consistent with an increased blood volume, because the peripheral resistance had returned to baseline at these time points. In one trial in urography, plasma volume was shown to increase maximally 8% at 3-5 min after injection of iohexol [41]. The small, early decrease in peak negative dP/dt is similar to that reported by others [35,37].…”
Section: Other Hemodynamic Variablessupporting
confidence: 83%
“…The late tendency for increased cardiac output is in agreement with data from other trials [2,34,38], and is also consistent with an increased blood volume, because the peripheral resistance had returned to baseline at these time points. In one trial in urography, plasma volume was shown to increase maximally 8% at 3-5 min after injection of iohexol [41]. The small, early decrease in peak negative dP/dt is similar to that reported by others [35,37].…”
Section: Other Hemodynamic Variablessupporting
confidence: 83%
“…Their lower osmolalities may offer image-quality improvements in intravenous digital subtraction angiography (DSA) as a result of lesser dilution of the contrast-agent bolus in the central blood volume (Hine et al, 1985).…”
Section: Clinical Usesmentioning
confidence: 99%
“…It can be minimised by placing the catheter as far centrally as possible, for example into the right atrium. Furthermore, it appears to be the case that the contrast agent itself, by a combination of osmotic effects and direct action on blood vessels, expands the central blood volume and produces a further deterioration in the contrast density-time curve and image quality (Hine, Lui & Dawson 1985, Burbank 1983). The use of a low osmolality contrast agent will reduce these effects.…”
Section: Introductionmentioning
confidence: 99%